Use of an Electronic Examination System (SPE) as a strategy for teaching and evaluation of learning: a case study at an Institution of Higher Education (IES) - Zonatto, Vinicius Costa da Silva; Silveira-Martins, Elvis; Dani, Andréia Carpes; Klann, Roberto Carlos (Revista de Administração da UFSM, 2016)
This study aims to identify the contributions of an Electronic Examination System of (SPE) in the processes of teaching and learning evaluation of Business and Accounting Undergraduate students of a higher education institution. A case study, of exploratory and descriptive nature, with qualitative and quantitative approach was conducted. The main highlighted contributions by teachers in the teaching and evaluation of learning processes are related to the identification of areas of improvement, the reinforcement of content taught during the course, the consolidation of basic concepts, the expansion of general knowledge (multidisciplinary learning), greater quality of education and higher levels of learning. The results show that the students’ performance on the SPE assessments was increasing, which represents a better performance of the whole group analyzed. Similar results were observed in bimonthly evaluations, where the students’ performance was also growing and lowest standard deviation, which indicates less dispersion in the overall performance of the students. The results suggest that the students’ are getting a better learning the content taught in courses, which opens perspectives for a new field of research. It is concluded that the SPE can be an effective strategy of teaching and learning.